2019
DOI: 10.1200/jco.2019.37.15_suppl.e16075
|View full text |Cite
|
Sign up to set email alerts
|

Real life data from Turkey regarding the impact of first-line sunitinib and pazopanib in metastatic renal cell cancer.

Abstract: e16075 Background: Although the distribution in the world varies widely, renal cell carcinoma (RCC) is the ninth most common cancer, especially in males. It’s the seventh most common cancer in Turkey. In this study, the progression-free survival (PFS) and overall survival (OS) of patients with metastatic RCC (mRCC) who were treated at 13 centers in our country were evaluated and the efficacy of first-line treatment approaches was compared. Methods: Data of mRCC patients admitted to 13 outpatient clinics in Tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A median PFS of 24.3 months was observed in the sunitinib arm, while a median PFS of 34.2 months was observed in the pazopanib arm. There was no statistically significant difference between the two drugs in terms of PFS [14].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…A median PFS of 24.3 months was observed in the sunitinib arm, while a median PFS of 34.2 months was observed in the pazopanib arm. There was no statistically significant difference between the two drugs in terms of PFS [14].…”
Section: Discussionmentioning
confidence: 72%
“…On the other hand, OS data from another study that compared pazopanib and sunitinib in the first-line treatment of mRCC showed pazopanib to be non-inferior to sunitinib, with median OS times for pazopanib and sunitinib reported as 26.9 months (95% CI, 23.1-35.6) and 26.1 months (95% CI, 20.7-31.6), respectively [13]. Considering the real-life data, in the study of Isik U. et al [14], sunitinib and pazopanib data were evaluated in first-line treatment in meta- static clear cell renal cell carcinoma. A median PFS of 24.3 months was observed in the sunitinib arm, while a median PFS of 34.2 months was observed in the pazopanib arm.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of RCC is increasing worldwide, with rates varying by age, race, sex and country (2). Also, it is the seventh most common cancer in Turkey (3).…”
Section: Introductionmentioning
confidence: 99%